PENGARUH NPL, LDR, ROA, NIM, BOPO, DAN CAR TERHADAP HARGA SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Sigit Prasetyo, 12.05.52.0080; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2016)
This research intend to examine and analyze the effect of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO), Capital Adequacy Ratio (CAR) to the stock price were listed on the Indonesia Stock Exchange in the period 2011-2015. The population on this research are the listed in Indonesia Stock Exchange that observed 2011-2015. The technique to determine sample is using purposive sampling method and the amount of selected sample are 155 companies. Analysis data technique that used regression analysis. The results of research have shown that variabels NPL, NIM, BOPO and CAR gives significant impact to stock price, otherwiswe LDR and ROA does not have significant effect on stock price.Keywords:Â NPL, LDR, ROA, NIM, BOPO, CAR, Stock Price